ANDIJON SHAHRIDA JAMOAT TRANSPORTI MUAMMOLARI. - Raximov Raxmatullo Rafiqjon o’g’li; Solimuhammadov Jamshidbek Sohibjon o’gli; Hoshimov O‘tkirbek Hakimjon o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2023)
In the article, what are the causes of problems in the public transport system in Andijan and how can they be solved? What is the practice in this regard abroad? Is it possible to implement foreign practices in Andijan? Concept?